Constructing, reproducing and challenging masculinities in a participatory intervention in urban informal settlements in South Africa. Issue 5 (3rd May 2020) - Gibbs, Andrew; Myrttinen, Henri; Washington, Laura; Sikweyiya, Yandisa; Jewkes, Rachel
Abstract: Participatory interventions with men and boys to transform masculinities are increasingly common to improve health and reduce intimate partner violence and HIV-related risk. Yet, despite this, there has been little consideration of how facilitators' own masculinities shape interventions. In this analysis of Stepping Stones and Creating Futures, a gender-transformative programme delivered to young men (aged 18–30 years) in urban informal settlements in Durban, South Africa we explore how facilitators' masculinities were employed to engender change in the masculinities of participants. We argue facilitators had to negotiate two tasks existing in some tension, the first, overt and the main aim of the programme: namely, challenging elements of the youthful masculinity at play in the lives of participants, such as exerting violent power over women. A second task was more covert: namely, establishing facilitators' credibility 'as men' in order to do this work with participants. Through strategies including clothes, mobile phones, jokes and storytelling, facilitators demonstrated to participants their 'successful' masculinity and could then engage with participants around emotions, non-violence and consistent condom use. This enabled facilitators and participants to undergo a limited processes of change, without 'compromising' their sense of masculinity, and without fundamentally challenging men's patriarchal privilege.